SNX27 links DGKζ to the control of transcriptional and metabolic programs in T lymphocytes - Tello-Lafoz, M. (Sci Rep, 2017)
Sorting nexin 27 (SNX27) recycles PSD-95, Dlg1, ZO-1 (PDZ) domain-interacting membrane proteins and is essential to sustain adequate brain functions. Here we define a fundamental SNX27 function in T lymphocytes controlling antigen-induced transcriptional activation and metabolic reprogramming. SNX27 limits the activation of diacylglycerol (DAG)-based signals through its high affinity PDZ-interacting cargo DAG kinase ζ (DGKζ). SNX27 silencing in human T cells enhanced T cell receptor (TCR)-stimulated activator protein 1 (AP-1)- and nuclear factor κB (NF-κB)-mediated transcription. Transcription did not increase upon DGKζ silencing, suggesting that DGKζ function is dependent on SNX27. The enhanced transcriptional activation in SNX27-silenced cells contrasted with defective activation of the mammalian target of rapamycin (mTOR) pathway. The analysis of Snx27 (−/−) mice supported a role for SNX27 in the control of T cell growth. This study broadens our understanding of SNX27 as an integrator of lipid-based signals with the control of transcription and metabolic pathways.